(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
This paper explores the challenges posed by the development of intercultural communicative competence (ICC) in relation to teacher training in the postcolonial Chilean context. Through a review of bibliographic sources it is recognized that the preparation of new teachers (indigenous and non-indigenous) has failed to transversely implement an intercultural educational approach. This has allowed Chile to keep the hegemony of eurocentric monoculturality, resulting in these teachers’ insufficient understanding of the cultures present in the classroom. In order to contribute to this critical discussion in the field, this paper reflects on the possibilities that ICC provides when seeking new ways of knowing and of communicating that confront monocultural education and develop intercultural educational processes, either in indigenous territories or in the new immigration contexts.